The Influence of Product Quality, Price and Word of Mouth on Hokido Brand Karate-Gi Purchasing Decisions in Five Dojos in DKI Jakarta Area - Hajir Masturi; Resti Hardini; Kumba Digdowiseiso; Nik Hazimah Nik Mat (International Journal of Social Service and Research, 2024)
This research aims to find out how big the influence of product quality, price, and word of mouth against the purchasing decisions of the karate-gi Hokido Brand in five Dojo regions DKI Jakarta population used in this study is that consumers ever buy karate-GI Hokido brand. The samples in this research were as many as 100 respondents. Sampling is done with non-probability sampling with a purposive sampling approach (with consideration of sampling) and Quota sampling (determination of samples from populations that have certain characteristics to the number of the desired quota is reached). The analysis method used was multiple linear regression analysis using the software SPSS 17.0. Results of the research show that the variable quality of products, prices, and word of mouth had a positive and significant effect on the purchasing decisions of karate-gi Hokkaido Brand in five Dojo Region DKI Jakarta.